The influence of carer fear and self-blame when supporting a loved one with an eating disorder. Issue 2 (14th March 2016) - Stillar, Amanda; Strahan, Erin; Nash, Patricia; Files, Natasha; Scarborough, Jennifer; Mayman, Shari; Henderson, Katherine; Gusella, Joanne; Connors, Laura; Orr, Emily S.; Marchand, Patricia; Dolhanty, Joanne; et al.
ABSTRACT: Carers often feel disempowered and engage in behaviours that inadvertently enable their loved one's ED symptoms and yet little is known regarding these processes. This study examined the relationships among fear, self-blame, self-efficacy, and accommodating and enabling behaviours in 137 carers of adolescents and adults with ED. The results revealed that fear and self-blame predicted low carer self-efficacy in supporting their loved one's recovery as well as the extent to which carers reported engaging in recovery-interfering behaviours. The relevance of these findings are discussed in the context of family-oriented ED therapies and highlight the importance for clinicians to attend to and help to process strong emotions in carers, in order to improve their supportive efforts and, ultimately, ED outcomes.